Bronchus-associated lymphoid tissue in lung transplantation: a facilitator of rejection or regulator of tolerance? - Wein, Alexander N.; Liu, Charles R.; Kreisel, Daniel (Frontiers in Immunology, 2025)
The role of bronchus-associated lymphoid tissue (BALT) in the regulation of immune responses to transplanted lungs remains an area of interest and controversy. Early studies in a rat pulmonary transplant model suggested BALT may accelerate rejection of grafts by inducing a local and systemic inflammatory response. Such observations were corroborated in intrapulmonary tracheal transplant models in the rat. While some human studies have described the presence of BALT in grafts that have been chronically rejected, others did not observe an association between induction of BALT and adverse outcomes. More recent investigations have found that BALT, enriched in immunoregulatory cell populations, is induced in tolerant mouse lung allografts, suggesting that such structures may be protective against rejection. Thus, the role of BALT in lung transplantation biology is complex. Insights gained from studies that focus on the role of BALT in lung transplantation may be harnessed to develop new therapies.